Breast cancer nursing interventions and clinical effectiveness: a systematic review. Issue 3 (4th June 2020) - Chan, Raymond Javan; Teleni, Laisa; McDonald, Suzanne; Kelly, Jaimon; Mahony, Jane; Ernst, Kerryn; Patford, Kerry; Townsend, James; Singh, Manisha; Yates, Patsy
Abstract : Objectives: To examine the effects of nurse-led interventions on the health-related quality of life, symptom burden and self-management/behavioural outcomes in women with breast cancer. Methods: Cochrane Controlled Register of Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline and Embase databases were searched (January 1999 to May 2019) to identify randomised controlled trials (RCTs) and controlled before-and-after studies of interventions delivered by nurses with oncology experience for women with breast cancer. Risk of bias was evaluated using the revised Cochrane risk-of-bias tool for randomised trials . Intervention effects were synthesised by cancer trajectory using The Omaha System Intervention Classification Scheme . Results: Thirty-one RCTs (4651 participants) were included. All studies were at risk of bias mainly due to inherent limitations such as lack of blinding and self-report data. Most studies (71%; n=22) reported at least one superior intervention effect. There were no differences in all outcomes between those who receive nurse-led surveillance care versus those who received physical led or usual discharge care. Compared with control interventions, there were superior teaching, guidance and counselling (63%) and case management (100%) intervention effects on symptom burden during treatment and survivorship. Effects of these interventions on health-related quality of life and symptom self-management/behavioural outcomes were inconsistent. Discussion: There is consistent evidence from RCTs that nurse-led surveillance interventions are as safe and effective as physician-led care and strong evidence that nurse-led teaching, guidance and counselling and case management interventions are effective for symptom management. Future studies should ensure the incorporation of health-related quality of life and self-management/behavioural outcomes and consider well-designed attentional placebo controls to blind participants for self-report outcomes. Protocol registration: The International Prospective Register of Systematic Reviews (PROSPERO): CRD42020134914).